Looking for Common Ground : Marine Living Resource Development in Alaska and Northern Norway in the Context of the Blue Economy - Tsiouvalas, Apostolos; Stoeva, Gergana; Raspotnik, Andreas (Sustainability, 2022)
Although the concept of the blue economy was created by the Small Island Developing States, its relevance extends to any coastal region around the globe, making the engagement of both state and corporate actors imperative. At the core of the blue economy framework stands the incorporation of ocean values and services into economic modeling and governance. Sustainable fisheries and aquaculture are thus significant in this endeavor, particularly for Arctic nations, the economies of which are predominantly based on seafood production. Yet, while focus is increasingly placed on sustainability and blue economy models among Arctic states, the need for structured transnational collaboration is not always acknowledged. In that respect, this article aims to articulate a comparative study of the status quo, challenges, and opportunities of fisheries and aquaculture in Alaska and northern Norway and seeks to explore potentials for cross-sectoral synergies between the two regions in the context of the blue economy. Looking for Common Ground: Marine Living Resource Development in Alaska and Northern Norway in the Context of the Blue Economy publishedVersion